2022
DOI: 10.3390/cancers14163887
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive Detection of GRP78 in Exosomes and Observation of Migration and Proliferation of Cancer Cells by Application of GRP78-Containing Exosomes

Abstract: Cancer cells communicate with each other via exosomes in the tumor microenvironment. However, measuring trace amounts of proteins in exosomes is difficult, and thus the cancer stemness-promoting mechanisms of exosomal proteins have not been elucidated. In the present study, we attempted to quantify trace amounts of 78-kDa glucose-regulated protein (GRP78), which is involved in cancer progression, in exosomes released from cultured gastric cancer cells using an ultrasensitive ELISA combined with thio-NAD cyclin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…We confirmed that the commercially available, easy-to-use kit, which was mentioned in Section 2.2 ., was useful for exosome isolation [ 3 , 4 ]. Using this kit, the exosomes were collected from the culture medium of GRP78-OE, GRP78-KD, and GRP78-mock AGS cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We confirmed that the commercially available, easy-to-use kit, which was mentioned in Section 2.2 ., was useful for exosome isolation [ 3 , 4 ]. Using this kit, the exosomes were collected from the culture medium of GRP78-OE, GRP78-KD, and GRP78-mock AGS cells.…”
Section: Resultsmentioning
confidence: 99%
“…Glucose-regulated protein 78 (GRP78) is involved in various aspects of cancer, such as invasion and metastasis [ 1 ], and GRP78 inhibitors are now considered potential cancer therapy targets [ 2 ]. In the tumor microenvironment, GRP78 contained in exosomes, transport vesicles of about 100-nm in size, is released from cancer cells [ 3 ], where it affects the surrounding cells and induces cancer malignancy [ 4 ]. Recent studies suggest that GRP78 also plays an important role in angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteins in exosomes may play an important role in the communication between cancer cells (or between cancer cells and normal cells) in the tumor microenvironment [14]. Measuring trace amounts of proteins in exosomes is difficult, however, and thus the cancer stemness-promoting mechanisms of exosomal proteins have not been elucidated.…”
Section: Contribution Of This Ultrasensitive Elisa To Cancer Researchmentioning
confidence: 99%
“…Measuring trace amounts of proteins in exosomes is difficult, however, and thus the cancer stemness-promoting mechanisms of exosomal proteins have not been elucidated. Our team attempted to quantify trace amounts of 78-kDa glucose-regulated protein (GRP78), which is involved in cancer progression, in exosomes released from cultured gastric cancer cells using the ultrasensitive ELISA [14]. We also evaluated the cancer stemness-promoting effects by applying high-GRP78-containing exosomes to cultured gastric cancer cells.…”
Section: Contribution Of This Ultrasensitive Elisa To Cancer Researchmentioning
confidence: 99%